2004
DOI: 10.1161/01.atv.0000125703.20434.4d
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Synthesis Correlates with the Posttranscriptional Regulation of the Sterol-Regulatory Element-Binding Protein

Abstract: Objective-Sterol-regulatory element-binding proteins (SREBPs) regulate transcription of genes of lipid metabolism.Ceramide decreases transcriptionally active SREBP levels independently of intracellular cholesterol levels. Mechanisms of the ceramide-mediated decrease of SREBP levels were investigated. T he sterol-regulatory element-binding proteins (SREBPs) are important transcription factors of genes of lipid metabolism. In sterol depletion, precursor SREBP is translocated from the endoplasmic reticulum by ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…In addition to the extracellular signaling mode, S1P and dihydro-S1P are utilized as intermediates in critical intracellular lipid metabolic pathways. For example, during de novo sphingolipid synthesis or metabolic breakdown of exogenously derived sphingolipids, metabolism of phosphorylated sphingoid bases by the S1P lyase enzyme is important in the downstream utilization of fatty acylCoA and phosphoethanolamine into complex phospholipid synthesis (47,48). In contrast to well characterized role of S1P, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the extracellular signaling mode, S1P and dihydro-S1P are utilized as intermediates in critical intracellular lipid metabolic pathways. For example, during de novo sphingolipid synthesis or metabolic breakdown of exogenously derived sphingolipids, metabolism of phosphorylated sphingoid bases by the S1P lyase enzyme is important in the downstream utilization of fatty acylCoA and phosphoethanolamine into complex phospholipid synthesis (47,48). In contrast to well characterized role of S1P, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not detect changes in total sphingomyelin levels in these cells (data not shown), it is possible that AMP-DNM treatment causes a disturbed balance in cholesterol and (glyco)sphingolipids in the ER membrane, (in)directly leading to SREBP activation. More recent studies have also shown that synthesis of sphingolipids in itself activates SREBP processing, independently of cellular cholesterol concentration (Worgall et al, 2002(Worgall et al, , 2004. Cholesterol-independent SREBP regulation is also found in Drosophila melanogaster, where SREBP levels are regulated by phospholipids instead of sterols (Rawson, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Recent findings demonstrated that inhibition of sphingolipid biosynthesis caused suppression of lipogenic gene expression in Chinese hamster ovary cells. 20 This hypothesis, however, needs further in vivo testing.…”
Section: Discussionmentioning
confidence: 99%